2000
DOI: 10.1007/s003600000109
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen requirements of the didelphid marsupial Caluromys philander

Abstract: The use of fruit-based diets by a small arboreal marsupial, the woolly opossum (Caluromys philander) was studied to elucidate the mechanisms used to compensate for a low dietary protein concentration. The passage of a liquid phase digesta marker (Cr-EDTA) through the gut was significantly faster when animals were fed a diet containing 0.45% N compared to that measured on a diet containing 0.90% N. The size of the gut of the two groups was similar except that the caecum of animals fed 0.45% N was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…In addition, previously we employed the same laboratory protocol and equipment on five primate species; this earlier work revealed extensive bacterial fermentation and methane production [49]. In short, it is our perspective that methodological concerns are mitigated by the facts that our research design and sample sizes are consistent with other studies [23], [28], [43], [44], [48], that no data exist on the digestive physiology of the study species (one of which is endangered: A. binturong ), and that even a small data set can help substantially to clarify the influence of digestion on feeding biology [1], [28], [59], [60].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, previously we employed the same laboratory protocol and equipment on five primate species; this earlier work revealed extensive bacterial fermentation and methane production [49]. In short, it is our perspective that methodological concerns are mitigated by the facts that our research design and sample sizes are consistent with other studies [23], [28], [43], [44], [48], that no data exist on the digestive physiology of the study species (one of which is endangered: A. binturong ), and that even a small data set can help substantially to clarify the influence of digestion on feeding biology [1], [28], [59], [60].…”
Section: Discussionmentioning
confidence: 78%
“…Other highly frugivorous mammal species (e.g., didelphid marsupials, pteropodid bats) maintain nitrogen balance by increasing total fruit intake (thereby increasing total dietary N intake) and decreasing retention times [3], [23]. However, increasing intake is done at the expense of digestive efficiency – i.e., extraction and uptake of macronutrients, especially carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in specimens of phalangerids from New Guinea, where diet quality is higher than that of Australian eucalypt species, the average distribution of GI tract length (Hume et al 1993) is similar to those recorded in the present study in T. vulpecula from southern New Zealand. Foley et al (2000) also reported a smaller caecum (by mass) in specimens of the South American woolly opossum (Caluromys philander) fed a diet containing 0.9% nitrogen compared to those animals fed a 0.45% nitrogen.…”
Section: Discussionmentioning
confidence: 88%
“…O único registro do Planalto Atlântico de São Paulo do espécime ocorreu em uma estrada próximo à floresta contínua. Já foi capturada em fragmentos de mata no Rio de Janeiro e Espírito Santo (Pires et al 2002, Pinto et al 2009) e em matas em diferentes estádios de regeneração de Minas Gerais, Espírito Santo e Guiana Francesa (Fonseca e Robinson 1990, Passamani 1995, Foley et al 2000, Grelle 2003, o que sugere que a espécie não tem preferência por matas maduras ou secundárias. Quatro indivíduos de Caluromys philander tiveram rádio colares instalados em pequenos fragmentos de Mata Atlântica no Rio de Janeiro e constatou-se uso esporádico das áreas abertas desmatadas do entorno dos fragmentos, compostas principalmente por gramíneas e samambaias ).…”
Section: Caracterização Do Uso De Habitats No Planalto Atlântico De Sunclassified
“…A espécie é provavelmente a mais arborícola das espécies de pequenos mamíferos não-voadores do Planalto Atlântico de São Paulo, como confirmam observações e diversas coletas quase exclusivamente no estrato mais alto amostrado e sempre acima do chão, variando de 1,5 até 20 m de altura (Passamani 1995, Foley et al 2000, Passamani 2000, Voss et al 2001, Grelle 2003, Gaspar 2005, Hannibal e Caceres 2010), além de uso de ninhos artificiais no sub-bosque e, preferencialmente, no dossel ) e observações de indivíduos escalando árvores quando liberados (Passamani 1995 (Atramentowicz 1995). O estro de fêmeas em laboratório foi influenciado por ferormônios masculinos através de urina ou através da aproximação com machos (Perret e Benmbarek 1991).…”
Section: Hábitounclassified